96.3k views
5 votes
(20 Points)

y = 4(x + 6)2 + 2
O y = -4x² + 48x + 136
O y = 4x2 + 48x + 146
O y = x² - 48x + 146
O y = -14x2 – 48x – 146

(20 Points) y = 4(x + 6)2 + 2 O y = -4x² + 48x + 136 O y = 4x2 + 48x + 146 O y = x-example-1
User Lazar
by
5.2k points

1 Answer

5 votes

Answer:

2nd option will be the answer (y=4x²+48x+146)

Explanation:

y=4(x+6)²+2

y=4(x²+2*x*6+6²)+2 [(a+b)²=a²+2ab+b²]

y=4(x²+12x+36)+2

y=4(x²)+4(12x)+4(36)+2

y=4x²+48x+144+2

y=4x²+48x+146

User Jeff Saremi
by
5.2k points